2016
DOI: 10.3233/jad-160325
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Immunoassay-Based Tools for the Comprehensive Quantification of Aβ40 and Aβ42 Peptides in Plasma

Abstract: Recent advances in neuroimaging and cerebrospinal fluid (CSF) biomarker assays have provided evidence of a long preclinical stage of Alzheimer’s disease (AD). This period is being increasingly targeted for secondary prevention trials of new therapies. In this context, the interest of a noninvasive, cost-effective amyloid-β (Aβ) blood-based test does not need to be overstated. Nevertheless, a thorough validation of these bioanalytical methods should be performed as a prerequisite for confident interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
(25 reference statements)
2
24
0
Order By: Relevance
“…In line with this, recent studies in CSF have reported better diagnostic performance for the Aβ42/40 ratio than for Aβ42 alone [42]. Furthermore, our approach allows a deeper knowledge of Aβ behavior in blood [32], by the assessment of Aβ bound to plasma components [43], [44], [45]. It is becoming increasingly clearer that sensitivity to cortical Aβ burden varied substantially among individuals and that the rate of SUVR change over time could be more relevant to predict disease progression than single cross-sectional measurements [46].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In line with this, recent studies in CSF have reported better diagnostic performance for the Aβ42/40 ratio than for Aβ42 alone [42]. Furthermore, our approach allows a deeper knowledge of Aβ behavior in blood [32], by the assessment of Aβ bound to plasma components [43], [44], [45]. It is becoming increasingly clearer that sensitivity to cortical Aβ burden varied substantially among individuals and that the rate of SUVR change over time could be more relevant to predict disease progression than single cross-sectional measurements [46].…”
Section: Discussionsupporting
confidence: 79%
“…Aβ40 and Aβ42 peptides were quantified using ABtest40 and ABtest42, respectively (Araclon Biotech Ltd. Zaragoza, Spain), being blinded to all participant characteristics at the time of analysis. Analytical procedures and performance characteristics of these tests are described elsewhere [32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean percentage calibration error was 2.2% for ABtest40 and 3.0% for ABtest42. The lower limit of quantification of the assays, empirically tested for precision and accuracy, are 7.6 pg/mL for ABtest40 and 3.6 pg/mL for ABtest42 [43]. All samples in our study were above these limits.…”
Section: Plasma Ab F42:f40 and Ab T42:t40 By Diagnostic Group And Ab mentioning
confidence: 65%
“…The anti A␤ x-40 and anti A␤ x-42 antibodies were purified by antigenaffinity chromatography using the same A␤ fragment inoculated to the rabbits (A␤ [33][34][35][36][37][38][39][40] and A␤ [35][36][37][38][39][40][41][42] , respectively). As described elsewhere, they have practically no cross-reactivity (less than 1%) between their target A␤ species nor with A␤ 1-38 (<2%), A␤ 1-43 (<1%) [31].…”
mentioning
confidence: 99%